01.12 Fra-1 transcription factor expression in macrophages foster inflammation during rheumatoid arthritis development. (1st March 2017) - Hannemann, Nicole; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Hueber, Axel; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Bogdan, Christian; Schett, Georg; et al.
Abstract : Background: The polarisation of macrophages leads to diverse populations, which are associated to a complex regulatory network of transcription factors. The activator protein (AP)−1 transcription factor family, specifically FOS proteins can regulate macrophage cytokines production. Because of the production of diverse pro-inflammatory and destructive molecules, macrophages are central players in chronic inflammation and bone destruction of rheumatoid arthritis (RA). Here, we delineate the diverse functions of Fra-1 and Fra-2 in the complex network of macrophage activations during RA development. Material and methods: To determine Fra-1 and Fra-2 roles during macrophage activation, Fra-1 or Fra-2 deficient peritoneal macrophages were used for microarray and quantitative real-time PCR analysis. In addition, promoter from genes found differentially expressed were analysed by chromatin immunoprecipitation (ChIP) analysis to discover directs targets of Fra-1 or Fra-2 in macrophages. To address the physiological roles of Fra-1 and Fra-2 in macrophages, the serum induced arthritis (K/BxN) model was applied to Fra-1 ΔMx or Fra-2 ΔLysM deficient mice. Results: Microarray analysis and subsequent gene ontology cluster enrichment highlight the specific role of Fra-1 during macrophages activation, whereas Fra-2 seems less essential for macrophage activated pathways. Additionally, the KEGG cluster analysis links Fra-1 expression to autoimmune diseases, such as RA. Applying the K/BxN serum transfer to Fra-2 ΔLysM or Fra-1 ΔMx mice, we could show that only Fra-1 deficient mice have a decreased arthritis severity, which was accompanied with a strong increased Arginase-1 (Arg1) expression in mice joints. Mechanistically, ChIP analysis confirmed that Fra-1 but not Fra-2 directly regulates Nos2 and Arg1 promoters in macrophages. Furthermore, the inhibition of Arg1 by Nω-hydroxy-nor-Arginine (NOHA) rescued the phenotype of Fra-1 mutant mice. Suggesting that Fra-1 promotes arthritic joint inflammation by inhibiting Arg1 expression, this probably leads to an increased resolution of inflammation in RA. Conclusion: We showed that Fra-1 defines the activation status of macrophages. Physiologically, Fra-1 regulates the Arg1/iNos axis thus promoting inflammation and bone destruction in RA. The role of Fra-1 in macrophages is unique, since Fra-2 cannot recapitulate Fra-1 functions. In conclusion, our data describe a new role of Fra-1 in macrophages activation in the maintenance of inflammation and joint destruction during acute RA.